Arsenic management in contaminated irrigation water for rice cultivation - Shah, A. L.; Naher, Umme Aminun; Hasan, Z.; Islam, S. M. Mofijul; Rahman, Muhammad Sajidur; Panhwar, Qurban Ali; Jusop, Shamshuddin (Universiti Putra Malaysia Press, 2016)
Arsenic (As) contaminated irrigation water (groundwater) is a threat to irrigated rice cultivation. Studies were conducted during three consecutive Boro seasons (fully dependent on irrigation) at highly As contaminated areas in Bangladesh to determine a suitable water management practice to reduce As accumulation in rice. In this study, two water management techniques were evaluated: 1) alternate wetting and drying (AWD) and continuous standing water (CSW) with surface (25 μg L-1 As); and 2) groundwater (419 μg L-1 As). A high yielding rice variety, BRRI dhan28, was grown. Results showed that the yield obtained by two management techniques were almost similar, except in CSW with groundwater application where significant yield reduction was observed. Significantly lower As content was found in the straw (77.23%) and rice grain (38.14%) of AWD with groundwater and CSW (straw 70.41% and 26.36%) with surface water application compared to CSW with ground water application. Among the water management practices, AWD with groundwater application showed similar benefit to CSW with surface water irrigation. Thus, alternate wetting and drying (AWD) with groundwater or surface water irrigation with CSW can be advocated as an appropriate agronomic practice for rice cultivated in As contaminated soils of Bangladesh.